Integration of geostatistical modeling into discrete event simulation for development of tailings dam retreatment applications. (1st April 2021) - Wilson, R.; Toro, N.; Naranjo, O.; Emery, X.; Navarra, A.
Highlights: Sustainable tailings management strategies are needed to address mining waste. Secondary mining of tailings for industrial materials is a viable remediation option. DES is a powerful tool to assess and mitigate operational risk in mining systems. Alternate modes of operation are critical to developing effective DES frameworks. Geostatistical heterogeneity can be suitably integrated into geometallurgy via DES. Abstract: Discrete event simulation (DES) is a computational tool capable of simulating the interplay of important variables and processes within complex mining systems that are subject to geological uncertainty. Alternate modes of operation are fundamental to the development of effective DES frameworks to model and monitor system performance in response to unexpected changes (e.g. ore feed attributes). The decision to switch between modes is governed by operational policy and is triggered as critical thresholds are crossed. Hundreds of operating days can be simulated to identify potential deficiencies, bottlenecks, or other operational risks. DES is thus useful to support strategic decision-making in the design, development and sustained operation of any mining system. Based on current mining trends, tailings storage facilities are growing in both size and number, resulting in alarming tailings accumulations worldwide. Coupled with a large number of abandoned legacy mines and artisanal mining operations, tailings and other waste materials pose a significant threat to human health and safety, as well as the environment. Cost-effective tailings management strategies to mitigate these risks through site remediation are required. Research on potential uses for discarded tailings is divided between secondary metallurgical processing for extractive purposes, and incorporation into industrial materials. The current framework has been adapted to integrate geostatistical variability into DES in order to assess the potential operational risks related to secondary mining of tailings for a conceptual cement production operation. A case study loosely based on data from a tailings dam in Taltal, northern Chile, is presented. Sample calculations are provided that demonstrate the framework as a valuable tool to evaluate and mitigate potential risk factors in the development of tailings retreatment applications.